Civil Asset Forfeiture Laws and Equitable Sharing Activity by the Police. Issue 1 (31st January 2018) - Holcomb, Jefferson E.; Williams, Marian R.; Hicks, William D.; Kovandzic, Tomislav V.; Meitl, Michele Bisaccia
Abstract : Research Summary: For several decades, critics have argued that civil forfeiture laws create incentives for law enforcement to increase departmental revenue by "policing for profit." By using data on federal equitable sharing payments to nearly 600 local law enforcement agencies between 2000 and 2012, we examine the relationship between the characteristics of state forfeiture laws and equitable sharing payments to local agencies. Our results indicate that agencies in states with state laws that are more restrictive or less rewarding to police collect more in federal equitable sharing. This finding supports the critics' argument that police behavior in regard to forfeiture activities is influenced by the financial rewards and burdens involved. Policy Implications: Our results reveal that the findings of investigative journalism and case study research, that is, that police forfeiture activities are influenced by financial rewards, may be more generalizable to law enforcement than previously thought. Despite recent state‐level reforms, federal equitable sharing and most state forfeiture laws provide limited due process protections and have minimal accountability or reporting requirements. Concerns about the impact of civil forfeiture practices on perceptions of procedural justice and police legitimacy are discussed, and possible policy reforms are reviewed.